An Interdisciplinary Approach to Connecting Quantitative and Science Curricula and Pedagogy in an Undergraduate Program. Issue 8 (14th September 2019) - Dame, L.; Aryal, B.; Huq, A.; Prat-Resina, X.
Abstract: Students entering health sciences programs may face challenges on their road to successful completion and possible entry to medical school in the area of preparedness in quantitative skills. At our institution, faculty analyzed evidence of these challenges including performance on the ACT Math Test, an in-house math placement test and quantitative tasks for physics and chemistry courses. The authors have used the ARCS (Attention, Relevance, Confidence, Satisfaction) conceptual framework developed by John M. Keller to examine a collaborative effort by our faculty from mathematics, chemistry and physics to design and deliver an interdisciplinary quantitative curriculum in the first 2 years. Preliminary results show high levels of attention, an improvement in student perceptions regarding the relevance of math to science, significant improvements to student confidence in their ability to learn and apply algebra, and reasons for student satisfaction. Faculty reflections indicate that this was a significant and rewarding effort.